2018
DOI: 10.1007/s10964-018-0827-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Examination of the Bullying-Sexual Violence Pathway across Early to Late Adolescence: Implicating Homophobic Name-Calling

Abstract: The Bully-Sexual Violence Pathway theory has indicated that bullying perpetration predicts sexual violence perpetration among males and females over time in middle school, and that homophobic name-calling perpetration moderates that association among males. In this study, the Bully-Sexual Violence Pathway theory was tested across early to late adolescence. Participants included 3549 students from four Midwestern middle schools and six high schools. Surveys were administered across six time points from Spring 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 48 publications
(76 reference statements)
5
53
0
3
Order By: Relevance
“…Moreover, bullying prevention efforts will likely be strengthened if they include traditional and cyber sexual harassment perpetration prevention messaging because a high‐risk subgroup exists that engages in both forms of aggression, and other research has also shown that bullying perpetration in early adolescence can be a precursor to sexual harassment perpetration (Espelage et al, , 2015). Starting early with a focus on primary prevention of bullying and sexual harassment might also prevent sexual violence in high school and adulthood (Espelage, Basile, Leemis, Hipp, & Davis, ; White & Smith, ). Our findings also suggest that program content addressing anger, conceptions of masculinity, pornography consumption, social support, school belonging, and parental monitoring in middle school may be particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bullying prevention efforts will likely be strengthened if they include traditional and cyber sexual harassment perpetration prevention messaging because a high‐risk subgroup exists that engages in both forms of aggression, and other research has also shown that bullying perpetration in early adolescence can be a precursor to sexual harassment perpetration (Espelage et al, , 2015). Starting early with a focus on primary prevention of bullying and sexual harassment might also prevent sexual violence in high school and adulthood (Espelage, Basile, Leemis, Hipp, & Davis, ; White & Smith, ). Our findings also suggest that program content addressing anger, conceptions of masculinity, pornography consumption, social support, school belonging, and parental monitoring in middle school may be particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of peers in perpetrating HB was confirmed in a subsequent and longitudinal study by Merrin et al (2018), where friendship selection was a relevant factor in determining an increasing or decreasing involvement in HB: Individuals preferred to befriend peers with similar rates of homophobic teasing, and changes in adolescent homophobic teasing were predicted by a concurrent homophobic teasing behavior of their friends. What these studies suggest is that group factors seem to be more predictive of HB than individual factors do (Birkett & Espelage, 2015), especially for adolescent males (Espelage, Basile, Leemis, Hipp, & Davis, 2018). Similarly, values and norms that regulate informal social relationships within a school, and the extent to which students share these values and norms with each other, have been found to affect students' behavior and their attitudes towards schoolmates (Foà, Brugman, & Mancini, 2012).…”
Section: School-level Factors Supporting Homophobic Bullyingmentioning
confidence: 93%
“…Homophobia is one of the main reasons for insulting, mocking, and rejecting classmates at school in Europe and is expressed through the use of homophobic language [22,23]. The use of this language goes far beyond sexual orientation and is also aimed at heterosexual youth [24,25], so it must be taken into account that, whether or not an individual belongs to a sexual minority, the existence of being labeled by the group as different is enough to initiate violent action.…”
Section: Introductionmentioning
confidence: 99%
“…The use of homophobic insults progressively increases from primary to secondary school, an educational stage where there is a high relationship between homophobic bullying and bullying [21,24,26,27], although they are different forms of school peer violence [24]. In relation to sex, the associations between bullying roles and use of homophobic language were different for girls and boys.…”
Section: Introductionmentioning
confidence: 99%